2018
DOI: 10.5937/specedreh17-18344
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in adults with intellectual disabilities: Objective indicators

Abstract: compared to male participants with ID, TD men had a higher total score (p=0.001), and better results in Health (p=0.021) and Productivity (p=0.000) domains. This result was also confirmed in female participants with the addition of TD women being significantly more successful in Intimacy (p=0.027) domain compared to women with ID. Statistically significant correlations among seven domains of QoL objective indictors in persons with ID were positive, ranging from moderate to high. The obtained results indicate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…This expressed satisfaction is likely due to limited ambitions and probably due to lack of perspectives in their lives. These findings are in keeping with previous studies 39,40,41 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This expressed satisfaction is likely due to limited ambitions and probably due to lack of perspectives in their lives. These findings are in keeping with previous studies 39,40,41 .…”
Section: Discussionsupporting
confidence: 93%
“…No statistical significant differences were found between total quality of life and gender. Kaliaca et al 39 did not find significant differences between dimensions of quality of life for males and females. The view that gender does not affect the total quality of life is supported by several researches 30,34 .…”
Section: Discussionmentioning
confidence: 84%
“…Otherwise, no studies have been found that analyse the link between gender and QoL specifically in the population with intellectual disabilities and mental health problems. However, there is some research that has found differences in QoL levels between men and women with intellectual disabilities who also present emotional lability (Kaljača et al, 2018; Mirón et al, 2008). These studies, as well as the present investigation, show a higher QoL among men.…”
Section: Discussionmentioning
confidence: 99%